Discovering the Digital Future: The Potential of Coding Education in Indonesia - Maspul, Kurniawan Arif (Jurnal Komputer Indonesia (Ju-Komi), 2023)
Coding education in Indonesia is critical in this age of rapid technological innovation. Coding provides learners with vital digital skills, promotes fairness in education, and improves learning outcomes. To discover the transformative influence of coding instruction, this qualitative study combines on-the-ground observation and a thorough literature review. This study adds to the body of knowledge and informs policymakers and educators by addressing equity discrepancies, evaluating their impact on learning outcomes, and proposing components for sustainable implementation. The findings argue for coding instruction in order to develop an inclusive and future-ready educational environment in Indonesia.